Intelligent Modeling System of E-commerce Consumption Behavior based on Distributed Data Integration Algorithm - Cao, Xiang (2022 International Conference on Edge Computing and Applications (ICECAA), 2022)
In this paper, a distributed heterogeneous data interoperability HIM model is designed by combining the main features of the two traditional data interoperability methods with the wide-area distributed environment. This model takes into account the advantages of both, and is more suitable for a wide-area distributed environment than using an integrated solution alone. This paper attempts to explore how the various factors affecting consumers' willingness to use in the original model indirectly affect the willingness to use through perceived trust. This paper collects valid data through questionnaire method, and uses SPSS19.0 statistical software to conduct empirical analysis on the data. On the basis of simple e-commerce connotation and development status, it analyzes consumer behavior in e-commerce environment, and discusses e-commerce environment. impact on consumer behavior.